Beyond Pressure Reduction: A Contemporary Review of Emerging Therapeutic Paradigms and Clinical Innovations in Glaucoma Management - Tyagi, Trisha; Dosad, Pooja; Singh, Vidya; Bhatt, Akrisht; Gupta, Muskan (Journal of Neonatal Surgery, 2025)
Glaucoma is still the main cause of irreversible blindness worldwide, impacting over 80 million eyes. The predictable treatment strategy has centred largely on falling intraocular pressure (IOP) through pharmacological, laser, and surgical treatments. But the recognition that glaucoma is progressive even in eyes with best IOP management has initiated new patterns of treatment beyond the traditional pressure-reduction therapy. This in-depth review examines novel therapeutic strategies in the treatment of glaucoma, with a focus on neuroprotection, gene therapy, artificial intelligence technology applications, regenerative medicine, and precision medicine strategies that represent paradigm shifts in modern glaucoma treatment. A systematic review of the literature was conducted on PubMed, Embase, and Cochrane databases, encompassing articles from 2019 to 2025. Keywords used were "glaucoma," "neuroprotection," "gene therapy," "artificial intelligence," "stem cell therapy," and "precision medicine." Recent evidence shows promising advancements in several therapeutic areas: neuroprotective interventions aimed at retinal ganglion cell sparing through BDNF, CNTF, and anti-apoptotic pathways; gene therapy strategies both for IOP decrease and neuroprotection; AI-based diagnostic and monitoring systems with diagnostic accuracy higher than 95%; regenerative medicine applications such as stem cell therapy and optic nerve regeneration; and precision medicine strategies involving pharmacogenomics and tailored risk assessment. The future of glaucoma treatment is shifting toward a multimodal strategy that blends conventional IOP-reducing treatments with neuroprotective, regenerative, and precision medicine techniques. These newer paradigms hold promise for salvaging vision in patients with glaucoma, especially those with normal-tension glaucoma or progressive disease in the setting of optimal IOP management. Keywords: glaucoma, neuroprotection, gene therapy, artificial intelligence, precision medicine, regenerative medicine.